2016
DOI: 10.1111/ans.13824
|View full text |Cite
|
Sign up to set email alerts
|

Interhospital transfer delays emergency abdominal surgery and prolongs stay

Abstract: Interhospital transfer delays surgical intervention and increases length of hospital stay. This mandates attention due to the implications for patient outcomes and added burden to the healthcare system. The system did, however, show capability to appropriately expedite surgery for acutely life-threatening cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 13 publications
1
20
0
1
Order By: Relevance
“…This finding underlines the time sensitiveness of surgical intervention in patients suffering from bowel ischemia. Transferring a patient from hospital to hospital will increase the delay to definitive care [ 7 ]. Based on the findings of the current study, in patients with bowel ischemia efforts should be made to shorten the prehospital time including avoidance of inter-hospital transfer.…”
Section: Discussionmentioning
confidence: 99%
“…This finding underlines the time sensitiveness of surgical intervention in patients suffering from bowel ischemia. Transferring a patient from hospital to hospital will increase the delay to definitive care [ 7 ]. Based on the findings of the current study, in patients with bowel ischemia efforts should be made to shorten the prehospital time including avoidance of inter-hospital transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the 910 adults patients in the study who underwent emergency abdominal surgery, 290 (31.9%) were transferred in from local district hospitals, had delayed surgical intervention (14.2h, p = 0.001), postoperative LOS 1.1 days (p = 0.001) and overall LOS 1.6 days (p < 0.001) -observed in all emergencies except peptic ulcer perforations. 24 Other reasons for delay include the time since the onset of illness because of late presentation due to lack of health care facilities, lack of health awareness, ignorance and poverty. 13,15 Late presentation and undue delay in operative intervention for SBO results in bowel ischaemia, increases the need for resection and the risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is debate about the causal factors, consistent among the majority of studies on surgical transfer is an observed increase in resource utilization for patients transferred for surgical care. 6,7 Much of this has been attributed to a delay in the time to definitive care associated with an increased pre-intervention hospitalization time. In our study, the preoperative length of stay at the operating facility was incrementally shorter in transfer patients compared to those admitted through the ED, with a median time to surgery of four days in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, associated with the transfer process itself is the potential for delays in care, longer hospitalizations, and increased patient and healthcare costs. 6,7 Prior work in the study of transfer networks within cardiac surgery has been limited. More commonly, transfer studies in cardiovascular disease have focused on the emergent situation such as in the management of ST segment myocardial infarction or aortic emergencies.…”
Section: Introductionmentioning
confidence: 99%